PENGARUH MEDIA ANIMASI BERBASIS ADOBE FLASH TERHADAP HASIL BELAJAR SISWA PADA MATERI JAMUR KELAS X - Tantri Herdianti; Kurnia Ningsih; Titin Titin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis research aims to know the influence of Adobe Flash-based animation media towards study result at the topic of fungi for students grade X MIA SMA Kemala Bhayangkari Kubu Raya. The research used quasy experimental with nonequivalent control group design. The population was  whole of  X MIA. The samples were taken by saturation sampling technique and decided X MIA 1 as experimental class and X MIA 2 as control class. The instrument was multiple choices consisted of 20 items. The average of  study result of experimental class was 15,10 and the control class was 13,50.  tcount>ttable (4,50>2,00) shows that there is a difference of study result between the students that taught by Adobe Flash-based animation media and taught by Power Point. ES shows that Adobe Flash-based animation media has high influence towards the study result at the topic of fungi and contribute 40,82%. Keywords:    Influence, Adobe Flash-Based Animation Media, Study Result and    Fungi